Transposition of the Extensor Indicis Proprius (EIP) for inveterate post-traumatic rupture of the Extensor Pollicis Longus (EPL) of the hand. 12 clinical cases - Sperati, Gianluca; Ceri, Lorenzo (Acta Biomedica Atenei Parmensis, 2019)
Background and aim of work: Subcutaneous tendon rupture of the Extensor Pollicis Longus (EPL) is one of the most frequent injuries of the extensor tendons of the hand. In this paper, we report our experience on 12 cases of atraumatic subcutaneous EPL lesions treated in our hospital with Extensor Indicis Proprius (EIP) transposition. Methods: This observational study was conducted between January 2015 and December 2018 in the Casa di Cura “Prof. Nobili”, Castiglione dei Pepoli (Bologna). Twelve patients were included in the study, nine of whom were females and three were males, with an average age of 72 years (range: 40-84 aa). The average follow-up was 32.4 months. The preoperative diagnosis was subcutaneous atraumatic rupture of the EPL tendon in all cases.  Results: The clinical outcome was excellent in all the patients at the end of follow-up. At the second clinical control, all patients achieved complete active extension of the distal phalanx of the first finger. We did not notice any intra- or extra-operative complications, and the post-operative course was regular in all cases. Conclusion: EIP transposition has allowed an almost complete recovery of the ability to extend the first finger in patients treated in our hospital, in line with what is described in the literature. In addition, patients’ satisfaction rate was excellent in all cases. Based on the good results and the low rate of complications affecting the donor area, we consider EIP transposition surgery to be a valid option for inveterate EPL ruptures.